The Effect of Saq Training on Developing Transitional Speed, Agility and Performance of Volleyball Reception Skill - Ali Hameed Ali AlZubaidi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The researcher used the experimental method in the pre- and post-measurement method. The number of training units reached was eight weeks, and the research sample consisted of ten players who represented the Najaf breeding team. The study's objectives were to determine the effect of SAQ training in developing transitional speed and agility among the Najaf breeding team and to determine the impact of these exercises in improving the skill performance of the skill of receiving volleyball. The study's findings, which were obtained using SPSS, indicated that SAQ exercises had a significant effect on the development of transitional speed and agility as well as improving the skill performance of the reception skill. The researcher suggested that physical and skill variables be given special attention because they are important in raising the level of performance of players. Additionally, the researcher suggested that SAQ training be given special attention because it is an effective training method in all situations of play to raise the physical and skill responses of volleyball players.